2018
DOI: 10.4244/eij-d-17-00962
|View full text |Cite
|
Sign up to set email alerts
|

A new optical coherence tomography-based calcium scoring system to predict stent underexpansion

Abstract: An OCT-based calcium scoring system can help to identify lesions that would benefit from plaque modification prior to stent implantation. Lesions with calcium deposit with maximum angle >180°, maximum thickness >0.5 mm, and length >5 mm may be at risk of stent underexpansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
202
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(223 citation statements)
references
References 17 publications
2
202
1
5
Order By: Relevance
“…As quoting from their manuscript: "we assigned 1 or 2 points to each of three conditions: 2 points for maximum calcium angle >180°, 1 point for maximum calcium thickness >0.5 mm, and 1 point for calcium length >5 mm." 13 In their study, they found that lesions with calcification score of 0 to 3 had "adequate stent expansion," whereas lesions with a score of 4 had "poor stent expansion. "…”
Section: Segmentation Refinement Strategymentioning
confidence: 97%
See 2 more Smart Citations
“…As quoting from their manuscript: "we assigned 1 or 2 points to each of three conditions: 2 points for maximum calcium angle >180°, 1 point for maximum calcium thickness >0.5 mm, and 1 point for calcium length >5 mm." 13 In their study, they found that lesions with calcification score of 0 to 3 had "adequate stent expansion," whereas lesions with a score of 4 had "poor stent expansion. "…”
Section: Segmentation Refinement Strategymentioning
confidence: 97%
“…Plaque length is the total length (number of frames × frame interval) over which the calcification spans. We used the method described by Fujino et al 13 for determining the stent deployment calcification score. The idea of calcification scoring is to define lesions that would benefit from plaque modification prior to stent implantation.…”
Section: Segmentation Refinement Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…With its higher spatial resolution and absence of acoustic shadowing, optical coherence tomography (OCT) offers a greater advantage over intravascular ultrasound in defining calcific burden not only in terms of degree of the calcific arch but also calcium thickness and length . This has been shown to provide crucial information for planning an upfront lesion preparation strategy to facilitate plaque modification and prevent stent underexpansion …”
mentioning
confidence: 99%
“…Em outros relatos, cálcios com espessura < 0,5 mm associaram-se com maior possibilidade de fratura durante dilatação com balão, independentemente da sua distribuição circunferencial, o que, por sua vez, resultou em melhor expansão dos stents implantados em comparação com os vasos em que não se obteve fratura dos cálcios (52,53) . Mais recentemente, Fujino e et al (54) desenvolveram um escore para graduação da calcificação coronária em uma coorte de 128 pacientes submetidos a TCO pré e pós implante de stents (coorte teste), validada em uma coorte externa de…”
Section: Placas Calcificadasunclassified